The monetary foundation of the economic circuit and the principle of effective demand in Marx, Keynes and Kalecki (2008)
Marx carried out the first full inquiry on the economics of the all-comprising circulation process of capital, first in Grundrisse in the late 1850s, and later in Capital and Theories of Surplus Value in the 1860s and the 1870s. Two substantial aspects are at the center of Marx's analysis: (a) the monetary determination of the social process of production and circulation of capital, i.e. the fact that money-capital is a social relation determining the interaction of agents in the monetary production economy alias capitalism; and (b) the notion of the economic circuit as the key economic category for the understanding of the monetary logic of the principle of effective demand. These aspects are also at the center of Keynes's and Kalecki's foundation of the theory of the monetary production economy.